2022
DOI: 10.1186/s12883-022-03027-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects and parameters of community-based exercise on motor symptoms in Parkinson’s disease: a meta-analysis

Abstract: Background Community-based exercise is a continuation and complement to inpatient rehabilitation for Parkinson's disease and does not require a professional physical therapist or equipment. The effects, parameters, and forms of each exercise are diverse, and the effect is affected by many factors. A meta-analysis was conducted to determine the effect and the best parameters for improving motor symptoms and to explore the possible factors affecting the effect of community-based exercise.  … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In one of the most recent meta-analyses on the effects of home-based exercise and PD, Yang et al's review reported a small effect across all types of exercise in relieving motor symptoms in PD patients, provided that the training period was no less than 8 weeks with no <30 training sessions within that period. 30 Hence, increasing exercise periods is indeed a promising recommendation for PD patients. However, the possible implications of exercise for oral health require more attention in future research, given the assumption that better oral self-care would be possible when motor symptoms are reduced due to physical training programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the most recent meta-analyses on the effects of home-based exercise and PD, Yang et al's review reported a small effect across all types of exercise in relieving motor symptoms in PD patients, provided that the training period was no less than 8 weeks with no <30 training sessions within that period. 30 Hence, increasing exercise periods is indeed a promising recommendation for PD patients. However, the possible implications of exercise for oral health require more attention in future research, given the assumption that better oral self-care would be possible when motor symptoms are reduced due to physical training programs.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the most recent meta‐analyses on the effects of home‐based exercise and PD, Yang et al. 's review reported a small effect across all types of exercise in relieving motor symptoms in PD patients, provided that the training period was no less than 8 weeks with no <30 training sessions within that period 30 . Hence, increasing exercise periods is indeed a promising recommendation for PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] It was reported that proper aerobic exercise training could potentially delay PD progression, and long-term community-and-home-based exercise interventions were demonstrated effective and safe for PD patients. [10][11][12][13][14] In addition, Flynn et al [12] reviewed and analyzed 16 clinical trials and concluded that home-based prescribed exercise achieved similar improvements to equivalent center-based exercise in terms of gait speed and balance-related activities in individuals with PD. Nonetheless, the specific mechanism underlying the exercise-induced positive effects in PD still warrants further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its versatility allows it to be practiced individually or in group settings, making it accessible to individuals with busy lifestyles and fostering social engagement 15 . Furthermore, Tai Chi requires no special equipment and can be enjoyed by virtually anyone, anywhere 16 .…”
Section: Introductionmentioning
confidence: 99%